ALC cleaning device / Nur Liyana Sujak … [et al.] - Sujak, Nur Liyana; Azizan, Nur Azfarah; Rasid, Nur Amira; Yaacob, Hidayati Mardhiah; Borhan, Atikah (2017)
Our team is developing a product which is 'Auto Laser Cleaner (ALC)'. This device can be used to clean the windows especially in high rise buildings. Besides, it was inspired from an aquarium robot cleaning. Compared to the current cleaner machine, this product has rapid cleaning action since it uses laser as the cleaning device. For safety features, this product has an anti-dropping algorithm thus limit the risk of it accidentally dropping from the window.